SOSIALISASI DAN PENYULUHAN PEMANFAATAN ENERGI TERBARUKAN DI LINGKUNGAN SMK TRI DARMA PALEMBANG (JURNAL PENGABDIAN KEPADA MASYARAKAT (ABDIMAS) UNIVERSITAS BATURAJA, 2021)
Electrical energy is one of the basic needs in human life. The available electrical energy comes from fossil energy whose supplies are running low. The purpose of this community service is to provide renewable knowledge, one of which is the use of solar energy as a renewable energy in everyday life. Community service activities for students of SMK Tri Darma Palembang in the form of socialization on the introduction of renewable energy sources, intelligence with the use of solar cells as an alternative energy, then demonstrating the use of solar cells in household electrical installations. At the time of demonstrating the PLTS, there were no running paths, the activities ran smoothly and the enthusiasm of the students of SMK Tri Darma was very high in paying attention and asking questions about the process of generating electricity using solar energy (PLTS) This community service activity was very beneficial for students at SMK Tri Dharma Palembang because the material presented at this community service is material that is not given to the lessons delivered at the SMK Tri Darma Palembang Energy Technology in the form of the use of new energy in everyday life.